2008
DOI: 10.1007/s10519-008-9203-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Selection Response for Contextual Fear Conditioning in a Cross Between C57BL/6J and A/J: Behavioral, QTL and Gene Expression Analysis

Abstract: We used short-term selection to produce out-bred mouse lines with differences in contextual fear conditioning. Within two generations of selection all low selected mice were homozygous for the recessive tyr c allele and showed the corresponding albino coat color. Freezing differed in the high and low selected lines across a range of parameters. We identified several QTLs for the selection response, including a highly significant QTL at the tyr locus (p < 9.6 −10 ). To determine whether the tyr c allele was dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…We confirmed a number of QTL that were previously identified using genetically diverse mouse populations derived from B6 and A/J. These include a Chromosome 1 (Chr.1) QTL (peaking at 70–80 cM) influencing open field activities (Gershenfeld and Paul, 1997), a Chr.1 QTL (peaking at ~75 cM) for body weight (Zhang and Gershenfeld, 2003), and a Chr.7 QTL (peaking at ~50 cM) co-localized with the albino ( Tyr ) locus influencing conditioned fear (Ponder et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…We confirmed a number of QTL that were previously identified using genetically diverse mouse populations derived from B6 and A/J. These include a Chromosome 1 (Chr.1) QTL (peaking at 70–80 cM) influencing open field activities (Gershenfeld and Paul, 1997), a Chr.1 QTL (peaking at ~75 cM) for body weight (Zhang and Gershenfeld, 2003), and a Chr.7 QTL (peaking at ~50 cM) co-localized with the albino ( Tyr ) locus influencing conditioned fear (Ponder et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…0.01 cutoff) have been identified in previous studies. These include, for example, SAMD4A, FGFR10P2, and CD99LD, which were identified during a selection response for contextual fear conditioning in rats using quantitative trait locus (QTL) and gene expression studies [Ponder et al, 2008]; KEK4, MUB and HSPB1 were identified in fruit flies selected for aggressive behavior [Dierick and Greenspan, 2006] and PEX19 and DEDD were identified proximal to a QTL hotspot on mouse chromosome 1 that modulates behavior [Mozhui et al, 2008]. Similarly, the long-term synaptic depression (LTD) pathway, one of the most overrepresented pathways revealed in our study, has been associated with predator threat.…”
Section: Discussionmentioning
confidence: 99%
“…Heritable differences in fear acquisition have already been established with selective breeding experiments (Radcliffe et al 2000; Ponder et al 2007, 2008; De Castro Gomes and Landeira-Fernandez 2008), and we wished to control for this factor in assessing whether differences in extinction learning have a heritable component. Moreover, differences in initial conditioned freezing can be generated by the incidental selection of arbitrary factors unrelated to emotional learning, such as general activity level or sensitivity to the tone or shock.…”
Section: Methodsmentioning
confidence: 99%